2007
DOI: 10.1038/nm1596
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of cone vision in a mouse model of achromatopsia

Abstract: Loss of cone function in the central retina is a pivotal event in the development of severe vision impairment for many prevalent blinding diseases. Complete achromatopsia is a genetic defect resulting in cone vision loss in 1 in 30,000 individuals. Using adeno-associated virus (AAV) gene therapy, we show that it is possible to target cones and rescue both the cone-mediated electroretinogram response and visual acuity in the Gnat2 cpfl3 mouse model of achromatopsia.The human retina has approximately 6 million c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
156
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(165 citation statements)
references
References 11 publications
6
156
0
3
Order By: Relevance
“…19,20 When a truncated version of the upstream sequences was incorporated into a recombinant adenoassociated viral vector (rAAV) of serotype-5 (rAAV5), this promoter targeted green fluorescent protein (GFP) expression to cones in the mouse, rat, ferret, guinea pig and squirrel monkey. [21][22][23] Glushakova et al 24 showed that elements of the human S-opsin promoter can preferentially target cones in rats, although specificity is limited and expression is promiscuous.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…19,20 When a truncated version of the upstream sequences was incorporated into a recombinant adenoassociated viral vector (rAAV) of serotype-5 (rAAV5), this promoter targeted green fluorescent protein (GFP) expression to cones in the mouse, rat, ferret, guinea pig and squirrel monkey. [21][22][23] Glushakova et al 24 showed that elements of the human S-opsin promoter can preferentially target cones in rats, although specificity is limited and expression is promiscuous.…”
Section: Introductionmentioning
confidence: 99%
“…Different promoters previously shown to confer cone photoreceptor expression were used to target GFP expression to the dog L/M and S cones. [19][20][21][22][23][24] Our results demonstrate poor expression levels, and lack of specificity with the human S-opsin promoter. In contrast, the red cone opsin promoters conferred a high degree of specificity, and expression robustness was dependent on the promoter length and content.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, both cone-mediated ERG response and visual acuity in a GNAT2 mouse model cpfl3 were rescued using targeted adeno-associated virus gene therapy. 33 Unraveling the genetic basis of the disease in the reported family is an essential step for future access to gene therapy. The GNAT2 mutations in nuclear families segregating with achromatopsia.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] In addition, therapeutic modalities have been demonstrated for other genetic subtypes of RP and LCA in a growing number of animal models, both of recessive and dominant forms of disease. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Notwithstanding such progress, the genetic complexity of this group of diseases represents a formidable logistic and economic hurdle in developing viable methods of prevention. Given this caveat, parameters effecting photoreceptor survival that are independent of the primary genetic lesion are critically important to identify.…”
mentioning
confidence: 99%